Longitudinal falls data in Parkinson's disease: feasibility of fall diaries and effect of attrition. Issue 19 (11th September 2018) - Hunter, Heather; Rochester, Lynn; Morris, Rosie; Lord, Sue
Abstract: Background: Identifying causes of falls for people with Parkinson's disease has met with limited success. Prospective falls measurement using the "gold standard" approach is challenging. This paper examines the process and outcomes associated with longitudinal falls reporting in this population. Methods: Participants were recruited from ICICLE-GAIT (a collaborative study with ICICLE-PD; an incident cohort study). Monthly falls diaries were examined over 48 months for accuracy of data and rate of attrition. To further inform analysis, characteristics of participants with 36-month completed diaries were compared with those who did not complete diaries. Results : One hundred and twenty-one participants were included at baseline. By 12 months, falls diary data had reduced to 107 participants; to 81 participants by 36 months; and to 59 participants by 48 months. Key reasons for diary attrition were withdrawal from ICICLE-gait ( n = 16) (13.2%), and noncompliance ( n = 11) (9.1%). The only significant difference between the completed and non-completed diary groups was age at 36 months, with older participants being more likely to send in diaries. Conclusions: Prospective falls data is feasible to collect over the long term. Attrition rates are high; however, participants retained in the study are overall representative of the total falls diary cohort. Implications for Rehabilitation: Understanding falls evolution in Parkinson's disease through consistent, personalized monitoring of falls events is critical to inform effective management. Our study shows that it is feasible to collect longitudinal falls data using "gold standard" methodology, although significant resources are required for implementation. We anticipate that our study methodology is broadly applicable to any at-risk falls cohort including older adults and diverse neurological conditions. Researchers and clinicians collating prospective falls data must ensure that participants understand what constitutes a fall, as per the World Health Organization definition. A second key point is to ensure prompt recording of any fall event.